2023
DOI: 10.4102/safp.v65i1.5616
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury among hospitalised patients who died due to COVID-19 in the Eastern Cape, South Africa

Abstract: Background: Acute kidney injury (AKI) commonly occurs in coronavirus disease 2019 (COVID-19) patients who have been hospitalised and is associated with a poor prognosis. This study aimed to determine the incidence of AKI among COVID-19 patients who died in a regional hospital in South Africa.Methods: This retrospective record review was conducted at the Mthatha Regional Hospital in South Africa’s Eastern Cape province. Data were collected between 10 July 2020 and 31 January 2021.Results: The incidence of AKI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(56 reference statements)
1
0
0
1
Order By: Relevance
“…The magnitude of AKI in our cohort was 42%, which is relatively high compared to other studies that found around 0.5–29% of hospitalized COVID-19 patients developed AKI [ 5 7 , 24 ]. However, our estimate is aligned with studies focused only on critically ill patients, of whom 38–45% developed AKI [ 8 , 9 , 11 , 25 ]. The high burden in our study may be attributed to the inclusion of only severe pneumonia cases requiring hospitalization.…”
Section: Discussionsupporting
confidence: 76%
“…The magnitude of AKI in our cohort was 42%, which is relatively high compared to other studies that found around 0.5–29% of hospitalized COVID-19 patients developed AKI [ 5 7 , 24 ]. However, our estimate is aligned with studies focused only on critically ill patients, of whom 38–45% developed AKI [ 8 , 9 , 11 , 25 ]. The high burden in our study may be attributed to the inclusion of only severe pneumonia cases requiring hospitalization.…”
Section: Discussionsupporting
confidence: 76%
“…Fisioterapia Brasil 2023;24(5);605-617 Já após receberam a capacitação, os profissionais destacaram que uma doença renal crônica poderia levar a um quadro mais grave de COVID-19. Vários estudos [16,17] relacionaram também o envolvimento renal na incidência de internações na Unidade de Terapia Intensiva (UTI) e mortes entre pacientes hospitalizados, porém ganharam destaque as lesões agudas, como insuficiência renal aguda e lesão renal aguda [17].…”
Section: Discussionunclassified